PERBANDINGAN METODE CIRC (COOPERATIVE, INTEGRATED, READING, AND COMPOSITION) DAN METODE SQ3R (SURVEY, QUESTION, READ, RECITE, AND REVIEW) TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN DAN HASIL BELAJAR SISWA KELAS V SEKOLAH DASAR - Hidayah, Nurul; Akhir, Muhammad; Bahri, Aliem (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research discussesd the Comparison CIRC (Cooperative, Integrated, Reading, And Composition) Method and SQ3R Method (Survey, Question, Read, Recite, And Review) on Reading Comprehension Ability and Learning Outcomes of Class V Students of Cluster 1 Elementary School, Tarowang District, Jeneponto Regency. This research aimed to determine whether there any differences in students’ reading abilities and learning outcomes using the CIRC learning method and the SQ3R learning method. The type of research used was quasy experimental design research with the Nonequivalent Multiple-Group Design type. The population in this study were all class V Cluster 1 Tarowang District which consists of three schools with a total 128 students. The research sample chosen was class V students UPT SD Negeri 4 Tarowang, totaling 40 students usingbo random cluster sampling technique. Data collection techniques in the research were carried out through test techniques to determine students’ reading comprehension abilities and learning outcomes in the form of multiple choice questions and descriptions of 20 questions, as well as observation sheets to find out the implementation of the CIRC method and the SQ3R method. The results of research based on descriptive analysis showed that the average value of the CIRC learning method was 84.50. Meanwhile, when applying the SQ3R learning method, an average score of 83 was obtained. This means that the CIRC learning method is more improved than the SQ3R learning method. Meanwhile, the results of the inferential analysis show that the CIRC learning method is more significant effect compared to the SQ3R learning method on the reading comprehension ability and learning outcomes of class V UPT SD Negeri 4 Tarowang students. This is based on the results of the paired sample t test obtained, namely the sig value. 0,001 < 0,005.